High-pass NGD characterization of resistive-inductive network based low-frequency circuit. Issue 5 (24th September 2021) - Guerin, Mathieu; Wan, Fayu; Gorshkov, Konstantin; Huang, Xiaoyu; Tishchuk, Bogdana; Sahoa, Frank Elliot; Chan, George; Baccar, Sahbi; Rahajandraibe, Wenceslas; Ravelo, Blaise
Abstract : Purpose: The purpose of this paper is to provide the high-pass (HP) negative group delay (NGD) circuit based (RL) network. Synthesis and experimental investigation of HP-NGD circuit are developed. Design/methodology/approach: The research work methodology is organized in three phases. The definition of the HP-NGD ideal specifications is introduced. The synthesis method allowing to determine the RL elements is developed. The validation results are discussed with comparison between the calculated model, simulation and measurement. Findings: This paper shows a validation of the HP-NGD theory with responses confirming NGD optimal frequency, value and attenuation of about (9 kHz, −1.12 µs, −1.64 dB) and (21 kHz, −0.92 µs, −4.81 dB) are measured. The tested circuits have experimented NGD cut-off frequencies around 5 and 11.7 kHz. Research limitations/implications: The validity of the HP-NGD topology depends on the coil self-inductance resonance. The HP-NGD effect is susceptible to be penalized by the parasitic elements of the self. Practical implications: The NGD circuit is usefully exploited in the electronic and communication system to reduce the undesired delay effect context. The NGD can be used to compensate the delay in any electronic devices and system. Social implications: Applications based on the NGD technology will be helpful in the communication, transportation and security research fields by reducing the delay inherent to any electronic circuit. Originality/value: The originality of the paper concerns the synthesis formulations of the RL elements in function of the expected HP-NGD optimal frequency, value and attenuation. In addition, an original measurement technique of HP-NGD is also introduced.